The Impact of Quality Rating and Improvement Systems on Families' Child Care Choices and the Supply of Child Care Labor - Chris M. Herbst (Institute for the Study of Labor (IZA), 2016)
Quality Rating and Improvement Systems (QRIS) are increasingly deployed by states to monitor and improve the quality of non-parental child care settings. By making information on program quality accessible to the public, QRIS attempts to alter parental preferences for quality-related attributes and encourage competition between providers. This paper draws on a variety of datasets to empirically characterize the way in which families and providers respond to the enactment of QRIS. Specifically, it exploits the differential timing in states' QRIS roll-out to examine two sets of outcomes: (i) families' child care choices and maternal employment and (ii) the supply and compensation of child care labor. Estimates from difference-in-differences models reveal several noteworthy findings. First, although QRIS induces families to shift from parental to non-parental care, economically disadvantaged families are more likely to use informal care, while their advantaged counterparts are more likely to use formal care. Second, QRIS increases the supply of high-skilled labor, particularly within the center-based sector. Third, all but the most highly-skilled child care workers experience rising compensation levels but also greater turnover. Finally, states that administer a wage compensation program alongside their QRIS experience larger increases in child care supply and compensation as well as lower turnover rates than states operating a QRIS in isolation.
Keywords: J13; J21; J22; J24; J3; 330; child care; quality rating and improvement systems